2018
DOI: 10.1111/mcn.12739
|View full text |Cite
|
Sign up to set email alerts
|

Aiming higher for maternal and child nutrition in South Asia

Abstract: The sustainable development of nations relies on children developing to their full potential and leading healthy, productive, and prosperous lives. Poor nutrition in early life threatens the growth and development of children, especially so in South Asia, which has the highest burdens of stunting, wasting, and anaemia in the world. Targeted actions to reduce stunting and other forms of child malnutrition in South Asia should be informed by an understanding of what drives poor nutrition in children, who is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…A mother of good nutritional status is likely to have healthier babies (Fuchs et al, 2014;Torlesse & Aguayo, 2018). Poor nutritional status was found to be a significant predictor for childhood acute malnutrition.…”
Section: Discussionmentioning
confidence: 95%
“…A mother of good nutritional status is likely to have healthier babies (Fuchs et al, 2014;Torlesse & Aguayo, 2018). Poor nutritional status was found to be a significant predictor for childhood acute malnutrition.…”
Section: Discussionmentioning
confidence: 95%
“… 11–19 Minimum dietary diversity is correlated with household wealth in South Asian countries. 20 , 21 Previous work has found that a minimum-cost nutritious diet would exceed current household food expenditure for most households in Bangladesh and Pakistan 14 , 16 and that the least-cost diet to satisfy dietary recommendations is unaffordable to approximately half of poor rural households in India. 18 …”
Section: Introductionmentioning
confidence: 99%
“…While among South Asian countries, Pakistan is ranked as having the highest prevalence of stunting (40.2%), wasting (17.7%) and underweight (28.9%) [2][3][4][5][6][7][8]. Inadequate breastfeeding and suboptimal complementary feeding practices are consistent predictors of malnutrition in the first 2 years of life [9]. This period has been recognized as the 'critical window of opportunity' for the promotion of optimal growth, health and development of a child [10].…”
Section: Introductionmentioning
confidence: 99%